Relevancy of modern democratic socialism to business environment (Global Business Management Review (GBMR), 2022)
In the past few decades, the supports towards the idea of Democratic Socialism especially among youth has skyrocketed. The exiting of Democratic Capitalist system which was adopted globally failed to narrow the class gap and is being viewed as constant economic and social exploitation by private companies. While past iteration of Socialism & Communism has been regarded as a major failure, it is still yet to be proven whether the ideas of Democratic Socialism will produce the same outcome. The main purpose of this paper is to offer a comprehensive study of Democratic Socialism which comprises its definitions, history, variations, and explanation on how democratic socialism is conducive to business environment. Methodology – This paper adopted qualitative research design paired with secondary sources data extraction for data collection process. Findings and Significance - This study is fundamental to the development of Democratic Socialism as a theory since it can be described not only as one of the vaguest theories but also as one with the biggest potential to business community. This paper provides at least a clear definition of what Democratic Socialism truly is and what its characteristics are. This paper also contributes to the body of knowledge on how few countries or governments managed to successfully assimilate the idea of Democracy and Socialism to form Democratic Socialism and put forward the relevance of democratic socialism to be practised in today’s world.